Uncertain empire : American history and the idea of the Cold War - Isaac, Joel, 1978-; Bell, Duncan, 1976- (Oxford University Press, 2012)
Historians have long understood that the notion of ""the cold war"" is richly metaphorical, if not paradoxical. The conflict between the United States and the Soviet Union was a war that fell ambiguously short of war, an armed truce that produced considerable bloodshed. Yet scholars in the rapidly expanding field of Cold War studies have seldom paused to consider the conceptual and chronological foundations of the idea of the Cold War itself. In Uncertain Empire, a group of leading scholars takes up the challenge of making sense of the idea of the Cold War and its application to the writing of.